Evaluation of the genotoxicity of neurotoxic insecticides using the micronucleus test in Tradescantia pallida. (July 2019) - de Morais, Cássio Resende; Pereira, Boscolli Barbosa; Almeida Sousa, Patrícia Cristina; Vieira Santos, Vanessa Santana; Campos, Carlos Fernando; Carvalho, Stephan Malfitano; Spanó, Mário Antônio; de Rezende, Alexandre Azenha Alves; Bonetti, Ana Maria
Abstract: Neonicotinoids and phenylpyrazoles are classes of neurotoxic insecticides which are able to bind at different ligand sites of neural receptors, leading to the deregulation of insect neural activity and hence resulting in death. The misuse or indiscriminate use of these chemicals is directly associated with several toxicological effects in biota and at different trophic levels. Based on this premise, the aim of the present study was to evaluate and compare the genotoxic capacity of different concentrations of thiamethoxam (TMX), acetamiprid (ACP), imidacloprid (IMI) and fipronil (FP) through the Micronucleus Test in Tradescantia pallida (Trad-MCN). After acclimatization (24 h), T. pallida stems were treated with stablished concentrations of TMX, ACP, IMI and FP for 8 h. Then, the stems of the model organism were submitted to a recovery phase (24 h). The young inflorescences were harvested and fixed in Carnoy solution and, after 24 h, were conserved in ethanol 70% until the analyzes. The obtained anthers were macerated on slides for microscopy, stained with acetic carmine dye and covered with coverslips before analysis by light microscopy. Considering the insecticides, the micronuclei (MN) frequency in plants treated at concentrations of 0.2 and 0.4 g L −1 for TMX, 0.2; 0.4 and 0.8 g L −1 for ACP, 0.1; 0.2; 0.4; 0.8 and 1.6 g L −1 for IMI and 0.2; 0.4; 0.8 and 1.6 g L −1 for FP differed statistically (p < 0.05, Tukey) from the MN frequency of the negative control. All chemicals evaluated revealed genotoxic activity in T. pallida at the highest concentrations. Graphical abstract: Image 1 Highlights: Genotoxicity of neurotoxic insecticides were evaluated at realistic concentrations. Highly used neurotoxic insecticides exhibited clastogenic and/or aneugenic effects. T. pallida shown to be an excellent model organism for screening induced genotoxicity.